A software application for E-Kanban-based WIP control in the aluminium industry. (1st January 2012) - Al-Hawari, Tarek; Aqlan, Faisal
In this paper, a software application for an E-Kanban inventory control system is developed to track work-in-process (WIP) inventory and finished goods in an aluminium factory. The current paper work system is replaced with an E-Kanban system that will minimise the errors prone paper forms as well as data entry requirements. Results show that manufacturing lead time and WIP have been reduced by an average of 88% and 50%, respectively. Accountability measure has been built into the system to identify the errors. Reports about any order can be generated and managers can make decisions based on real-time information.